Functionalized Hexahydropyrrolo[2, 1‐b]oxazoles from Catalyst‐Free Annulation of Δ1‐Pyrrolines with Electron‐Deficient Propargylic Alcohols. Issue 27 (8th June 2020) - Oparina, Ludmila A.; Shabalin, Dmitrii A.; Mal'kina, Anastasiya G.; Kolyvanov, Nikita A.; Grishchenko, Lyudmila A.; Ushakov, Igor' A.; Vashchenko, Alexander V.; Trofimov, Boris A.
Abstract : Electron‐deficient propargylic alcohols (EWG = CN, C(O)Ph, CO2 Me, C(O)NH2 ) under catalyst‐free mild conditions are annulated with Δ1‐pyrrolines to afford functionalized hexahydropyrrolo[2, 1‐b]oxazoles, mostly in 19–93 % yield. The synthesis is stereoselective with respect to disposition of functionalized ethenyl group relative to the condensed heterocyclic system thus formed in most cases. This methodology provides a simple one‐pot access to a novel family of synthetically and pharmaceutically prospective. Abstract : Catalyst‐free annulation of Δ1‐pyrrolines with electron‐deficient propargylic alcohols was demonstrated allowing the formation of functionalized hexahydropyrrolo[2, 1‐ b ]oxazoles in good to excellent yields.